2001
DOI: 10.1046/j.1469-8137.2001.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and nitrogen uptake of CO2‐enriched rice under field conditions

Abstract: Summary• The effects of elevated CO 2 are reported here on the uptake of nitrogen (N) and its relationships with growth and grain yield in rice ( Oryza sativa ).• Using free-air CO 2 enrichment (FACE), rice crops were grown at ambient or elevated ( c . 300 µ mol mol -1 above ambient) CO 2 and supplied with low, medium or high levels of N.• For the medium and high N treatments, FACE increased N uptake at panicle initiation but not at maturity. For total dry matter, as well as spikelet number and grain yield, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
128
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(151 citation statements)
references
References 21 publications
21
128
2
Order By: Relevance
“…Our fi nding that ear weight was increased by CO 2 enrichment agrees with previous reports (Kimball, 1983(Kimball, , 1986Kim et al, 2001). Although increased photosynthesis has been reported under long-term CO 2 enrichment (Baker et al, 1990b;Monje and Bugbee, 1998;Sakai et al, 2001), the infl uence of CO 2 enrichment on carbohydrate translocation has been reported by only a few researchers (e.g., Grüters, 1999).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our fi nding that ear weight was increased by CO 2 enrichment agrees with previous reports (Kimball, 1983(Kimball, , 1986Kim et al, 2001). Although increased photosynthesis has been reported under long-term CO 2 enrichment (Baker et al, 1990b;Monje and Bugbee, 1998;Sakai et al, 2001), the infl uence of CO 2 enrichment on carbohydrate translocation has been reported by only a few researchers (e.g., Grüters, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…In another study conducted in a paddy fi eld (Kim et al, 2001), the amount of 13 C translocated to the roots was less than 1 % of the 13 C supplied at the time of heading (data not shown). We also measured the amount of fallen leaves every 30 days, but the data cannot be presented here, because the difference between plants grown under normal and CO 2 -enriched conditions was so small and because the amount of leaves fallen during the 9-day study period was negligible in our analysis of 13 C translocation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, biomass gains from CO 2 elevation can be preserved if ample N is supplied to crops. Kim et al (2001) grew rice in a FACE experiment and found that, to maximize rice grain yield under elevated CO 2 , it was important to supply sufficient N over the whole season. The implication for agriculture is the need to increase crop fertilization to ensure that growth enhancement by CO 2 will not be limited by nutrient supply.…”
Section: Introductionmentioning
confidence: 99%
“…Yin [9] reported that both leaf mass-based N content and specific leaf area decreased under elevated CO 2 in their meta-analysis of 62 species. Kim et al [10] recommended that a sufficient supply of N be maintained over the entire rice growing season to maintain increased dry matter production and thus maximize grain yields under enriched CO 2 . Wu et al [11] reported that CO 2 level significantly influenced foliar total amino acids in cotton plants, and foliar protein content significantly decreased under elevated CO 2 compared with ambient CO 2 .…”
mentioning
confidence: 99%